The effect of gamma radiation on in vitro regeneration of Capsicum annuum L. var. Kulai / Nur Amalina Farhana Shariffudin - Shariffudin, Nur Amalina Farhana (2016)
Capsicum annuum (C annuum) var. Kulai has been difficult to work on in vitro as compared to other Solanaceous crop based on the capability to regenerate shoot. Mutagenesis technique was applied using gamma ray in order to enhance the regeneration of C. annuum via in vitro. In this study, seeds of C. annuum were irradiated with various doses of gamma ray (0, 20, 40, 60, 80, 100, 200, 300, 400, 500, and 600 Gy) at Agensi Nuklear Malaysia (ANM) and were grown in vitro on MS medium without hormone to obtain hypocotyl and cotyledon as explant in the next experiment. The experimental design was completely randomized design (CRD) with 5x5. Overall seed germination rate revealed significant variation whereby seeds start to germinate from 6 to 17 days. Seed exposed with 0, 20, 40 and 60 Gy germinated in less than 10 days on the media. A total of 50 explants including hypocotyl and cotyledon were cultured on MS medium with 20 different concentrations of BAP in combination with AgNC>3. For higher gamma doses of 200 Gy to 600 Gy, the explants were not well developed and further study on these treatments were not carried out. Almost 90% of both explants in all treatments induced callus. Callus characteristics formed were greenish friable, greenish compact, yellowish watery, yellowish friable and yellowish compact. Callus in some treatment also produced unique colour such as purple (20 Gy on treatment 3.0 mg/L BAP and 2.0 mg/L AgNCO₃), bright yellow (60 Gy cotyledons on treatment 3.0 mg/L BAP and 4.0 mg/ L AgNCO₃) and bright yellowish orange (40 Gy cotyledons on treatment 2.0 mg/L BAP and 3.0 mg/ L AgNCO₃). Some callus originated form seeds irradiated with 40 Gy, 60 Gy and 80 Gy produced direct and indirect organogenesis in which a few of them promote root and hairy root. Shoot regeneration was observed from cotyledon explant from treatment 60 Gy, 80 Gy and 100 Gy on MS media supplemented with 5.0 mg/L BAP and 3.0 mg/ L AgNCO₃ and also treatment 80 Gy on MS media supplemented with 4.0 mg/L BAP alone. Meanwhile for the hypocotyl culture, shoot regeneration was observed in the treatment 40 Gy with 3.0mg/L BAP alone. Different cell structures in callus and roots were determined through analysis using Scanning Electron Microscope. Gamma irradiation at higher gamma doses (200, 300, 400, 500 and 600 Gy) showed no promising results at the early stage in vitro and optimization of shoot regeneration were not successful due to the recalcitrance characteristic of C. annuum. Most of the explants only produced callus with different characteristics.